2013
DOI: 10.1063/1.4788927
|View full text |Cite
|
Sign up to set email alerts
|

Probing viscosity of nanoliter droplets of butterfly saliva by magnetic rotational spectroscopy

Abstract: Articles you may be interested inExtensional flow of hyaluronic acid solutions in an optimized microfluidic cross-slot devicea) Biomicrofluidics 7, 044108 (2013); 10.1063/1.4816708 Shear and dilatational linear and nonlinear subphase controlled interfacial rheology of β-lactoglobulin fibrils and their derivatives Reduction of low-density lipoprotein cholesterol, plasma viscosity, and whole blood viscosity by the application of pulsed corona discharges and filtration Rev. Sci. Instrum. 84, 034301 (2013); 10.106… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 23 publications
0
60
0
Order By: Relevance
“…Submitted to a rotating magnetic field with increasing angular frequency, the behavior of the wires immersed in viscous and in viscoelastic fluids is modeled. The rotational phase diagram exhibits a transition between a synchronous and an asynchronous regime, this second regime being characterized by a backand-forth motion [18,24,[26][27][28]. The instability resembles that observed on laboratory benches when a viscous solution is actuated with a magnetic bar.…”
Section: -Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Submitted to a rotating magnetic field with increasing angular frequency, the behavior of the wires immersed in viscous and in viscoelastic fluids is modeled. The rotational phase diagram exhibits a transition between a synchronous and an asynchronous regime, this second regime being characterized by a backand-forth motion [18,24,[26][27][28]. The instability resembles that observed on laboratory benches when a viscous solution is actuated with a magnetic bar.…”
Section: -Conclusionmentioning
confidence: 99%
“…In recent studies, the case of the Newton fluid was evaluated [18,24,[26][27][28]. It was shown that for frequency above the wire undergoes an hydrodynamic instability between two rotation regimes [32,33].…”
Section: -Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in 1950, Frances Crick monitored the rotational motion of micron sized aspherical particles in response to pulsed magnetic fields to measure the viscosity in chick fibroblasts [21]. Optical tracking of rotating magnetic particles was used to monitor changes in drag during growth of single bacteria on MagMOONs [22] to monitor changes in shape of single cancer stem cells [23], to measure the viscosity of butterfly saliva [24], and to detect bacteria based on changes in viscosity when bacteria excrete biofilm polymers [25]. In addition, particle rotation has been used to track intracellular transport [26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…5). In these calculations, the viscosities of sucrose solutions were measured by magnetic rotational spectroscopy (Tokarev et al, 2013) and the densities of the sucrose solutions were taken from published values (Asadi, 2005) (Table 2).…”
Section: Suction-pump Pressurementioning
confidence: 99%